Peran Kepala Desa Dalam Pemberdayaan Masyarakat Petani di Desa Kota Bangun Ilir Kecamatan Kota Bangun Kabupaten Kutai Kartanegara - Muhammad Miftah Farid (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
This study aims to identify and analyze the role of the village head in empowering farmers in Kota Bangun Ilir Village, Kota Bangun District, Kutai Kartanegara Regency and to identify the inhibiting factors. This type of research uses qualitative research and data collection by means of interviews, observation and documentation, while the informant technique uses a purposive sampling technique as resource persons, namely the Head of Service, staff, community or visitors. The data analysis used is an interactive model developed by Milles and Huberman. The results showed that the role of the Village Head of Kota Bangun Ilir had been carried out well, which was identified from the awareness stage, the socialization carried out by the Village Head such as training on giving vitamins to farmers' plants was effective. The community transformation stage is given an understanding through the Village Head program to broaden horizons and provide basic skills regarding rice farming so that they can take a role in society through rice farming. Through the improvement stage, the village head has provided appropriate programs such as honing community skills and skills through outreach so that innovative initiatives and capabilities are formed to deliver independence. The inhibiting factors for the village head's role in empowering farmers are the lack of community participation and budget constraints.